Microvascular anastomosis using Ankaferd blood stopper: demonstration of long-term histopathologic effects on vascular tissue - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
Ankaferd blood stopper (ABS) (Ankaferd Flag Kozmetik Turkey) is a medicinal plant extract, which is used in Turkish traditional medicine as a haemostatic agent The aim of this study was to investigate the haemostatic effect of ABS in preventing microvascular leakage on an anastomosis site and to look into its long-term impact on vascular tissue. Twenty-one Wistar albino rats were randomly divided into three groups. The animals in the second and third groups were pretreated with acetylsalicylic acid. All of the right femoral arteries were divided and anastomosed in an endto-end fashion. Following microvascular anastomosis, saline-soaked gauze tampons were applied in the first and second groups. In the third group, ABS-soaked tampons were applied to the anastomosis sites. The mean bleeding time of group 3 was significantly shorter than group 2 and group 1. Three weeks after the operation, there were aneurysms on all of the anastomosis sites in group 3 and none of the anastomoses were patent. Histologic examination demonstrated increased inflammatory cell infiltration, tunica media degeneration and contraction of tunica intima in group 3. This is the first study reporting the long-term effects of ABS on microvascular anastomosis. Contrary to previously reported studies, this agent is not appropriate for use on injured or anastomosed vessels. Blood Coagul Fibrinolysis 25:721-725 2014 (C) Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins.
Keywords: Ankaferd; end-to-end anastomosis; haemostasis; INTERRUPTED SUTURE TECHNIQUES; BLEEDING MODEL; EXTRACT; GLUE; L.